THE EFFECCT OF INITIAL WATER DEPTH ON THE PERFORMANCE OF A SINGLE SLOPE SOLAR STILL IN YOLA, NIGERIA - A, Alkasim,; A.B., Dikko,; A.D., Ahmed, (IJRDO-Journal of Applied Science, 2017)
The distillation of shallow-well brackish water by the use of solar still is one of the promisingmethods adopted in arid zones. The population increase, economic development, in addition toglobal warming are creating imbalance between supply and demand of fresh water. Manydeveloping countries faces the challenge of accessing the portable water for uses in homes andclinics despite the availability of sun shine in these regions. In this paper, a single-basin singleslope solar still was design and constructed in Yola Nigeria (longitude 13oE, latitude 9.23oN)the Daily distillate was 1.49 litres at an initial water depth of 3.0 cm and 3.3 litres at an initialwater depth of 0.5 cm. A maximum average efficiency of 28% was obtained. The performanceevaluation for different initial water depths (0.5 cm, 1.0 cm, 1.5 cm, 2.0 cm, 2.5 cm and 3.0cm) reveals that the daily cumulative yields are 3306 ml. 2616 ml, 2224 ml, 2006 ml, 1698 ml,1493 ml, 1490 ml, respectively.